IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT ) DI KELURAHAN TEMBONG KECAMATAN CIPOCOK JAYA - Anggita Nurafia; Rina Yulianti; Arenawati Arenawati (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2020)
There are several problems in the Non-Cash Food Assistance Program (BPNT) in Tembong Village, Cipocok Jaya District, Serang City, among others: poor understanding of the Duties, Principals and Functions of Regulations Regarding BPNT Program Distribution in Tembong Village, causing the condition of the available human resources to be of poor quality in implementing the program. BPNT, the socialization of the Non-Cash Food Assistance Program (BPNT) has not been carried out optimally so that the community is not aware of the existence of the Non-Cash Food Assistance Program (BPNT) in the Tembong Kelurahan, the attitude of the implementers of the Non-Cash Food Assistance Program (BPNT) in the Tembong Kelurahan is still less responsive. The purpose of this study was to find out how the attitude of the implementation of the non-cash food assistance program (BPNT). The theory used is the implementation theory of Van Metter and Van Horn, the research method used is qualitative. The results of this study The implementation of the Non-Cash Food Assistance Program (BPNT) has not run optimally because of the lack of available budget that makes the socialization process uneven and the facilities and infrastructure experience problems when distribution Keywords: Policy Implementation, Non-Cash Food Assistance Program (BPNT)